TRANSFORMATIONAL LEADERSHIP AFFECTING EMPLOYEE MOTIVATION IN SAHAPATHANAPIBUL PUBLIC COMPANY LIMITED - Vijchulata, Chanin; Ngamkana, Prapaswat; Tungjai, Sujidtra (Journal of MCU Phetchaburi Review, 2025)
Research Objective 1) to study the transformational leadership level and motivation. 2) to compare the motivation of employees’ works operations. Classified by personal factors. 3) to study the factors that influence the motivation of employees of Sahapattanaphibul Public Company Limited. The sample was 400 employees of Sahapatanapibul PLC. The transformational leadership level in overall, with a high level. Employee motivation of Sahapatanapibul is average at a high level 2) age, position and average monthly income differ in the motivation of employees of Sahapatanapibul public company limited. 3) Motivational factors are idealized influence, inspirational motivation, intellectual stimulation and individualized consideration affects the motivation of employees, the employees of Sahapatanapibul public company limited. The variables can explain the change in the motivation of employees of Sahapatanapibul public company limited by 47.40%.